Soziale Systeme : Zeitschrift für soziologische Theorie (De Gruyter Oldenbourg, 1995)
Soziale Systeme is a journal at the interface of systems theory and sociological theory with a broad interest in developments in sociological theory. It promotes a wide intellectual perspective characterized on the one hand by the inclusion of interdisciplinary aspects (cybernetics, biological systems theory, the theory of evolution) and, on the other hand, by maintaining sociology's unique conceptual identity as an academic discipline.